2007
DOI: 10.1016/j.febslet.2007.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Valproate induces apoptosis by inducing accumulation of neutral lipids which was prevented by disruption of the SIR2 gene in Saccharomyces cerevisiae

Abstract: We investigated the participation of HDACs in VPA induced apoptosis in Saccharomyces cerevisiae. VPA (20 mM) induced apoptosis in several HDAC mutants, including PRD3 and HDA1-disrupted cells and SIR2 over expressing cells, as well as in wild-type cells but not SIR2-disrupted cells. Intracellular reactive oxygen species and neutral lipid content increased markedly in all kinds of HDAC mutant cells tested except for SIR2-disrupted cells. Thus, these results suggest that 20 mM VPA induces neutral lipid accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…We found that low pH strongly potentiated the growth-inhibiting properties of VPA, in accord with published studies documenting pH-dependent VPA-induced growth inhibition and apoptosis in S. pombe 53. VPA-induced apoptosis has also been reported in S. cerevisiae, although these data were generated using YPD medium (which is normally at higher pH than SC) over long time periods, i.e., 24 h or more1112. Yca1 (a caspase-like protease) and the class III HDAC Sir2 are required for apoptosis in response to VPA in budding yeast1112.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that low pH strongly potentiated the growth-inhibiting properties of VPA, in accord with published studies documenting pH-dependent VPA-induced growth inhibition and apoptosis in S. pombe 53. VPA-induced apoptosis has also been reported in S. cerevisiae, although these data were generated using YPD medium (which is normally at higher pH than SC) over long time periods, i.e., 24 h or more1112. Yca1 (a caspase-like protease) and the class III HDAC Sir2 are required for apoptosis in response to VPA in budding yeast1112.…”
Section: Discussionsupporting
confidence: 90%
“…VPA-induced apoptosis has also been reported in S. cerevisiae, although these data were generated using YPD medium (which is normally at higher pH than SC) over long time periods, i.e., 24 h or more1112. Yca1 (a caspase-like protease) and the class III HDAC Sir2 are required for apoptosis in response to VPA in budding yeast1112. While we did not formally test whether VPA caused apoptosis under our conditions, deletion of YCA1 and SIR2, or other proapoptotic genes ( FIS1, BXI1, KEX1 ; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that metacaspase did not play a role in the death of S. pombe cells induced by VPA. A defect in Sir2, which encodes a NAD-dependent histone deacetylase, 30) made S. cerevisiae cells resistant to VPA, 31) while the S. pombe strain with the sir2 mutation was as sensitive to VPA as the wild type both on plates and in liquid culture (Fig. 6B).…”
Section: Defects In Metacaspase and Sir2 Did Not Affect Sensitivity Tmentioning
confidence: 99%
“…39 Moreover, low doses of valproic acid, an inhibitor of histone deacetylases (HDACs) in mammalian cells, which displays antitumor activity and is extensively used to treat neuropsychiatric disorders, induces YCA1-dependent yeast apoptosis, 35 which is prevented upon deletion of the HDAC SIR2. 40 Treatment of yeast cells with amiodarone also triggers yeast cell death, in this case via the mitochondrial pathway and preceded by a Ca 2 þ boost. 36 The transcriptional response of yeast cells to amiodarone treatment includes two signatures: one that resembles a Ca 2 þ stress response that is accompanied by downregulation of genes involved in all stages of cell-cycle control, and another that is Ca 2 þ -independent and affects nutrient-responsive genes.…”
Section: Triggering Yeast Apoptosismentioning
confidence: 99%